Strategies to Increase Organizational Resilience through Strengthening Entrepreneurial Spirit, Communication Effectiveness and Visionary Leadership - Ibrahim, Iman; Hardhienata, Ing Soewarto; Setyo Pranowo, Agus (Dinasti Publisher, 2025)
This study aims to analyze the factors that influence the success of micro, small and medium enterprises (MSMEs) in Bogor City, focusing on the role of venture capital and the quality of human resources (HR). The research also identifies the main constraints of MSMEs and develops strategic recommendations for sustainable development. Using a quantitative approach and SITOREM analysis, the study involved 197 respondents selected through multi-stage random sampling. Primary data were collected through questionnaires, while secondary data were obtained from online sources. Path analysis revealed that entrepreneurial spirit has a positive significant influence on visionary leadership, while communication effectiveness has no significant direct influence. Furthermore, entrepreneurial spirit and communication effectiveness significantly influence organizational resilience, both directly and through the mediation of visionary leadership. The SITOREM analysis identified priority indicators for improvement, such as entrepreneurship training and more effective communication. The study concludes that risk capital, quality of human capital and visionary leadership play an important role in strengthening the resilience of MSMEs. Recommendations include developing human resource training, increasing access to capital, and improving the effectiveness of internal communication. The findings of this study contribute significantly to the development of strategies to improve the competitiveness and sustainability of MSMEs in the face of modern economic challenges.